2020
DOI: 10.1104/pp.19.01501
|View full text |Cite
|
Sign up to set email alerts
|

Class-I TCP Transcription Factors Activate the SAUR63 Gene Subfamily in Gibberellin-Dependent Stamen Filament Elongation

Abstract: In autogamous plants like Arabidopsis (Arabidopsis thaliana), stamen filament elongation must be finely regulated to ensure that anthers reach the pistil at the correct developmental stage. In this work, we studied the roles of Arabidopsis TEOSINTE BRANCHED1, CYCLOIDEA, PCF15 (TCP15), and related class-I TCP transcription factors in stamen filament elongation. Plants with decreased expression of class-I TCPs and plants that express a fusion of TCP15 to a repressor domain (pTCP15::TCP15-EAR) had shorter stamens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 61 publications
(121 reference statements)
0
39
0
Order By: Relevance
“…GmSRS18, as a transcription factor, was located in the cell nucleus, which showed that it functions in cell nucleus. Transcription factors were involved in the abiotic and biotic stress response in many plants [67][68][69][70][71][72]. Though there are few reports of SRS family about the abiotic stress response thus far, we demonstrated that GmSRS18 can increase the transgenic Arabidopsis sensitivity to drought and salt stresses.…”
Section: Discussionmentioning
confidence: 70%
“…GmSRS18, as a transcription factor, was located in the cell nucleus, which showed that it functions in cell nucleus. Transcription factors were involved in the abiotic and biotic stress response in many plants [67][68][69][70][71][72]. Though there are few reports of SRS family about the abiotic stress response thus far, we demonstrated that GmSRS18 can increase the transgenic Arabidopsis sensitivity to drought and salt stresses.…”
Section: Discussionmentioning
confidence: 70%
“…GhTCP14 is a crucial regulator in auxin-mediated elongation of cotton fiber cells [ 16 ]. In Arabidopsis , TCP15 is induced by gibberellins (GAs) and TCP1 is a positive regulator of the brassinosteroid (BR) biosynthesis pathway [ 21 , 22 ]. Besides, TCPs also participate in ethylene, strigolactone (SL) and cytokinins (CK) biosynthesis [ 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most loss-of-function mutants of class I TCP genes exhibit mild or no defective phenotypes due to genetic redundancy [9]. Even so, several class I TCP transcription factors have been integrated into multiple hormone-signaling pathways and participated in the regulation of inflorescences stem elongation [27], gynoecium development [28], seed germination [15], filament elongation of stamen [29] and flowering [13] in Arabidopsis. AtTCP20 binds to the GCCCR motif of the CYCB1 promoter and participates in the regulation of cell division, cell expansion and growth coordination [30].…”
Section: Introductionmentioning
confidence: 99%